Strategies in Developing MSMEs of Pematangsiantar - Annisa Edelia; Zuhrinal M Nawawi (International Journal Labs, 2021)
The purpose of this study was to determine the development strategi of Micro Small and Medium Enterprises (UMKM) in Pematangsiantar City. The research model is qualitative approach. The research design is field study and literature study. The focus of research to be achived is the development strategy of Small Micro and Medium Enterprises in Pematangsiantar city. The data analysis technique used is descriptive qualitative analysis. The result of the study show that UMKM enterpreneurs face obstacles in developing their businesses. The strategy of developing UMKM in Pematangsiantar City is inseparable from the participation of the government and UMKM actors. The government should be able to provide assistance to UMKM actors, as well as socialization and training, and UMKM actors should be more creative and innovative in producing goods.